2008
DOI: 10.1016/j.neuron.2007.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Active Dendritic Conductances Dynamically Regulate GABA Release from Thalamic Interneurons

Abstract: Inhibitory interneurons in the dorsal lateral geniculate nucleus (dLGN) process visual information by precisely controlling spike timing and by refining the receptive fields of thalamocortical (TC) neurons. Previous studies indicate that dLGN interneurons inhibit TC neurons by releasing GABA from both axons and dendrites. However, the mechanisms controlling GABA release are poorly understood. Here, using simultaneous whole-cell recordings from interneurons and TC neurons and two-photon calcium imaging, we find… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
154
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(168 citation statements)
references
References 70 publications
13
154
0
1
Order By: Relevance
“…The ascending fibres from the brainstem and the corticofugal axons are capable of controlling the strength and pattern of intrathalamic inhibitory mechanisms [106,176,177]. GABA release in these interneurons occurs in both axons and dendrites and while Na + APs evoke widespread Ca 2+ signals throughout dendritic and axonal arbours, Ca 2+ spikes mediated by L-type Ca 2+ channels specifically trigger dendritic GABA release [1]. These Na + and Ca 2+ spikes regulate the rapid and prolonged release of GABA from interneurons, determining spatial and temporal features of the feedforward inhibition [11].…”
Section: Intrinsic Properties Of Thalamic Interneuronsmentioning
confidence: 99%
“…The ascending fibres from the brainstem and the corticofugal axons are capable of controlling the strength and pattern of intrathalamic inhibitory mechanisms [106,176,177]. GABA release in these interneurons occurs in both axons and dendrites and while Na + APs evoke widespread Ca 2+ signals throughout dendritic and axonal arbours, Ca 2+ spikes mediated by L-type Ca 2+ channels specifically trigger dendritic GABA release [1]. These Na + and Ca 2+ spikes regulate the rapid and prolonged release of GABA from interneurons, determining spatial and temporal features of the feedforward inhibition [11].…”
Section: Intrinsic Properties Of Thalamic Interneuronsmentioning
confidence: 99%
“…Once the axon threshold is exceeded, conducted action potentials are intensity independent. The all-or-none character of ST intensity-recruitment relations indicates a reliance on activation of single axons impinging on individual neurons (1,8). For testing, shock intensities were finely graded above and below threshold to establish the threshold value for the onset of reliably evoked responses.…”
Section: St Stimulus Intensity-recruitment Relationsmentioning
confidence: 99%
“…Whether these specific subtypes can be selectively activated by synaptic afferents remains unclear, but could have important consequences on our understanding of mGluR-dependent actions on thalamocortical processing. This is an relatively important issue consider that over the last several years, the independence between the distal events and somatic activity of the dLGN interneurons has been questioned based on studies indicating that somatic events can backpropagate into the dendritic arbor of the interneurons [19,29,30]. The functional significance of these differences is further discussed below ( Local vs.…”
Section: Regulation Of Dendritic Outputs Via Multiple Neuromodulatorsmentioning
confidence: 99%
“…Several different approaches including electrical stimulation of synaptic inputs, local pressure application of pharmacological agonists, and photo-uncaging of caged glutamate have demonstrated that iGluR activation produces a short-lasting robust increase in potential F2 output. The iGluR-dependent response has a short latency and relatively short duration (typically <100ms) [19]. In contrast, the mGluR-dependent response has a longer latency and can have a duration of tens of seconds [21].…”
Section: Regulation Of Dendritic Outputs Via Multiple Neuromodulatorsmentioning
confidence: 99%
See 1 more Smart Citation